Creep and breakage behavior of broken rock in the caved zone of abundant mines under triaxial compression condition. (November 2022) - Meng, Fanfei; Pu, Hai; Dintwe, Tumelo K.M.; Sasaoka, Takashi; Xu, Junce
Abstract: It is essential to deeply understand the deformation behavior of overburden above the goaf after mining for the ecological restoration of abandoned mines and the reuse of underground space. Due to the large voids and complex structures, the broken rock in the caved zone is sensitive to time effects, and the deformation behavior is the most complicated. Therefore, a self-made broken rock specimen was made which can freely deform in the lateral direction and withstand confining pressure. A series of rheological tests were performed on these specimens under various confining pressures, axial pressures, and gradations. The research results show that the creep behavior of broken rock undergoes decelerated creep or stable creep stages, depending on its level of axial pressure, and there is no accelerated creep stage. Compared with the confining pressure, the axial pressure plays the main role in the creep deformation of the specimen. Moreover, the broken rock gradation of the triaxial creep experiment affects the relative breakage index B r . When the proportion of rock blocks of the original gradation increases with the particle size of each group, the relative breakage index B r is the largest; on the contrary, it is the smallest. The relative breakage index B r is positively correlated with the confining pressure. In addition, a fractional-order creep model for broken rock in the caved zone of the goaf was proposed, and its fitting results are better than those of the classical Burgers model. Based on the proposed fractional-order creep model, a long-term subsidence prediction model of the caved zone after mining is also proposed, which can provide a theoretical basis for the long-term stability analysis of the abandoned mine.